Social enterprise in western Europe theory, models and practice - Defourny, Jacques; Nyssens, Marthe (Routledge studies in social enterprise and social innovation, 2021)
"In the last two decades, the quest for a widely accepted definition of social enterprise has been a central issue in a great number of publications. The main objective of the ICSEM Project on which this book is based was to show that the social enterprise field would benefit much more from linking conceptualisation efforts to the huge diversity of social enterprises than from an additional and ambitious attempt at providing an encompassing definition. Starting from a hypothesis that could be termed "the impossibility of a unified definition", the ICSEM research strategy relied on bottom-up approaches to capture the social enterprise phenomenon in its local and national contexts. This strategy made it possible to take into account and give legitimacy to locally embedded approaches, while simultaneously allowing for the identification of major social enterprise models to delineate the field on common grounds at the international level. Social Enterprise in Western Europe -the third volume in a series of four ICSEM-based books on social enterprise worldwide - will serve as a key reference and resource for teachers, researchers, students, experts, policy makers, journalists and others who want to acquire a broad understanding of the social enterprise and social entrepreneurship phenomena as they emerge and develop in this region"--